A modified diet to support conservation of the Atala hairstreak butterfly (Eumaeus atala Poey). Issue 5 (14th June 2021) - Braatz, Elizabeth; Sincage, Jamie; Gezon, Zachariah J.; Maynard, Lily T.; Ardente, Amanda; Savage, Anne; Sullivan, Kathleen E.; Livingston, Shannon; Valdes, Eduardo V.
Abstract: Raising insects in a laboratory for release into the wild is a common conservation practice, but maintaining breeding colonies year‐round can be limited by seasonal food availability. Food availability is particularly challenging for insects which depend on specific host plants. For example, our early efforts to rear the imperiled Atala hairstreak butterfly ( Eumaeus atala Poey) resulted in colony failure during winter due to lack of food. To overcome this barrier, we developed a modified freeze‐dried host plant diet to support the colony. The diet consisted of reconstituted freeze‐dried leaves and stems from fresh‐growth coontie ( Zamia integrifolia ), the host plant for the Atala butterflies. We fed larvae less than 9 mm on this freeze‐dried diet and transferred them to live coontie plants after they were more than 9 mm. We reared a colony of Atala butterflies using these methods for 859 days, resulting in more than 3400 animals released into the wild. Comparing colony counts during that time period to the 548 days we reared them without modified freeze‐dried diet showed a clear benefit in using freeze‐dried diet. A growth trial ( N = 40) of larvae fed on only freeze‐dried diet compared to larvae fed on fresh coontie cuttings found no significant difference in larval or pupal development between groups ( p = 0.71 and p = 0.47, respectively). We, therefore, conclude that the freeze‐dried diet provided an appropriate alternative for Atala colonies when fresh growth from the host plant is unavailable, and we recommend use of this technique for raising other host plant‐dependent insect species of conservation concern. Graphical abstract: Graphical abstract created by Jennifer Torchalski, Disney's Animals, Science and Environment, Lake Buena Vista, Florida, USA. RESEARCH HIGHLIGHTS: When rearing butterflies ex situ for conservation, many species of butterflies are highly host‐plant specific, and it can be difficult to provide enough food for them during nongrowing seasons After a colony failure due to food shortage, we created a modified freeze‐dried diet for the imperiled Atala hairstreak butterfly ( Eumaus atala ) using methods that could potentially be replicated for other butterflies The diet was highly successful, leading to the rearing and release of over 3800 adult butterflies back into the wild Key to the methods was using pure, new‐growth host plant, and switching larger larvae back to mature leaves